Implementation of E-Health Based Technology to Improve the Health Status of the Elderly: A Literature Review - Filipus Y. Boibalan; Sukihananto (LPPM STIKES Al-Ma'arif Baturaja, 2024)
The number of elderly from year to year continues to increase, this has a significant impact on health services. The significant addition of the elderly and the worsening of the situation including decreased health, altered emotional status, inability to do activities independently make some people consider the elderly a burden. Objective: Providing ideas and ideas from the results of literature review on the implementation of E-health-based technology to improve the health status of the elderly, using smartphones to measure elderly activities, security and safety of the elderly. The method used in this research is literature review with keywords namely